Association of CCL7 Promoter Polymorphism with Responsiveness to Allergen in Cynomolgus Macaque Model of Asthma - Sela Septima Mariya; Fitriya Nur Annisa Dewi; Eric Hayes; Villiandra Villiandra; Yasmina Arditi Pramastri; Diah Iskandriati; Uus Saepuloh; Joko Pamungkas; I Nengah Budiarsa; Dondin Sajuthi (The Indonesian Biomedical Journal, 2020)
BACKGROUND: C-C motif Ligand 7 (CCL7) has been reported to be associated with asthma severity in humans. Cynomolgus macaques (Macaca fascicularis; Mf) are often used as animal model of asthma but little is known about Mf genetic profile such as polymorphism. Our aim was to identify CCL7 polymorphism in Mf as a potential surrogate marker for identification of allergen responsiveness in the Mf model of asthma.METHODS: Real-time PCR was performed on archive of bronchoalveolar fluid samples previously collected from Mf that were exposed to allergen. Expression of CCL7 mRNA was evaluated, and sequencing technique was used to identify polymorphism in this gene.RESULTS: The results showed that CCL7 expression did not differ between Mf, despite a trend of lower expression in Mf that exhibited high response to allergen. By direct DNA sequencing of CCL7, 10 sequence variants were identified; three in promoter region (-460 G/A, -459 A/G, -456 -/A ), two in exon 1 (9 A/G, 65 G/C), four in intron 1 (135 T/C, 254 T/C, 420 T/C, 453 A/G), and one in intron 2 (1205 T/A).CONCLUSION: There was an association between Mf sensitivity to allergen with CCL7 promoter polymorphism at (-456 -/A). These results suggest that CCL7 may be a potential genetic marker to identify Mf sensitivity to allergen, which could be a useful tool to efficiently select for Mf model of asthma.KEYWORDS: asthma, CCL7, allergy, Ascaris suum, nonhuman primate